- PENGGUNAAN LAGU “AKU MAU” PADA PRODUK MAINAN BONEKA “PUTRI ANISA HIJAB PERFUMED DOLL”: - - Felicitas Citra Permatahati Nainggolan; Bustani, Simona (Faculty of Law, Universitas Trisakti, 2024)
Copyright violations have occurred frequently over the years, with one prevalent issue being the unauthorized duplication of copyrighted works. A notable instance of this is the unauthorized use of the song